2020
DOI: 10.1186/s43046-020-0016-x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma (HCC) in Egypt: A comprehensive overview

Abstract: Background: Worldwide, hepatocellular carcinoma (HCC) is a universal problem and its epidemiological data showed variation from place to place. Hepatocellular carcinoma (HCC) is the sixth and fourth common cancer in worldwide and Egypt, respectively. Egypt ranks the third and 15 th most populous country in Africa and worldwide, respectively. The aim of this review is to compare the status of HCC in Egypt to that in the worldwide from different issues; risk factors, screening and surveillance, diagnosis and tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
183
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 208 publications
(186 citation statements)
references
References 104 publications
3
183
0
Order By: Relevance
“…In addition to liver resection and liver transplantation, targeted therapy, immunotherapy and transarterial chemoembolization are used to treat advanced HCC (5)(6)(7). However, patients with HCC suffer from a high prevalence of mortality and recurrence (5,(7)(8)(9)(10)(11). Thus, identification of novel effective targets for the treatment of advanced HCC remains essential.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to liver resection and liver transplantation, targeted therapy, immunotherapy and transarterial chemoembolization are used to treat advanced HCC (5)(6)(7). However, patients with HCC suffer from a high prevalence of mortality and recurrence (5,(7)(8)(9)(10)(11). Thus, identification of novel effective targets for the treatment of advanced HCC remains essential.…”
Section: Introductionmentioning
confidence: 99%
“…Liver malignancy is the sixth commonest malignancy worldwide with an incidence of approximately 841,000 new cases in 2018 [1], of which hepatocellular carcinoma (HCC) represents 80% [2], and considered the fourth leading cause of cancer-related death worldwide [3]. In Egypt, HCC is the fourth common cancer [4].…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Epidemiological studies have shown that the highest incidence rates of HCC occur in developing countries, with endemic hepatitis B virus (HBV) and/or hepatitis C virus (HCV) infections, exerting an increasing load on health care budgets. [ 1,2 ] The currently available treatment strategies for HCC include surgical interventions and local radiotherapy that are beneficial only for early‐stage patients with localized liver tumors who show a good response to the treatment and have a good survival rate. On the other hand, treating advanced stages of HCC is much more difficult and the survival rate has not significantly improved in the past three decades.…”
Section: Introductionmentioning
confidence: 99%